Pemanfaatan Limbah Plastik menjadi Produk Kreatif bagi Pemuda di Pulau Salemo Desa Mattiro Bombang - Hakim, Irma; Noerfitryani, Noerfitryani; Marwal, M. Rafid; Rosanna, Rosanna; Wahyu, Farhanah; Asdi, Asdi (Jurnal Pengabdian UNDIKMA, 2022)
The purpose of this community service activity is to increase the knowledge and skills of partners in managing plastic waste into creative products on Salemo Island. The partners of this service are youths who are less productive who are members of the Joint Rezki Fisherman Group. The implementation of this activity consists of several stages, namely providing materials, interviews, demonstrations of making plastic waste products, monitoring, and evaluating activities. The results of this service activity are an increase in the knowledge and skills of partners regarding waste management techniques, producing waste products made from plastic into valuable products, and the formation of partner business working groups. The types of plastic waste products produced are wall hangings, tissue holders, pencil or pen holders, bags, decorative lights, accessories containers, cellphone chargers, and piggy banks.